Organic and inorganic fertilization with and without microbial inoculants in peat-based substrate and hydroponic crop production - Nelson, Jason Scott (Kansas State University, 2013)
Liquid organic fertilizers and microbial inoculants of beneficial microorganisms are garnering interest from commercial greenhouse growers who seek to produce crops more sustainably, but research about their efficacy is limited and results are conflicting. This research focused on comparing the effect of microbial inoculant addition in two soilless crop production systems under organic versus conventional fertilization. Two experiments were conducted with impatiens (Impatiens walleriana) in a peat-based substrate and four experiments were conducted with butterhead lettuce (Latuca sativa) in nutrient film technique (NFT) hydroponics. In the impatiens studies, nitrogen, phosphorus, and potassium were incorporated pre-plant equally across treatments using OsmocoteTM, or organic fertilizers Bloodmeal or Feathermeal. An inorganic constant liquid feed (CLF) was also evaluated. Microbial inoculants that contained a variety of beneficial species, including Bacillus spp. and Trichoderma spp. were drench-applied at the beginning of the cropping cycle. Impatiens growth was comparable between the nutrient regimens in one of the studies. CO2 respiration was measured on substrate samples. At a 5X application rate, inoculants contributed to subtle increases in plant growth in organic treatments, but microbial activity was unaffected as measured by CO2 respiration. However, organic nutrient sources contributed to higher CO2 respiration at day 7 of the production cycle compared to inorganic nutrient sources. The hydroponic trials consisted of inorganic and organic nutrient regimens, evaluated with and without microbial inoculant addition. Nutrient analyses and CO2 respiration of the nutrient solutions were collected. Use of inoculants resulted in increased plant growth when used in organic nutrient regimens in some trials. Plant dry weight and CO2 respiration in the inorganic nutrient regimens were increased in certain instances with inoculant addition. No differences in mycorrhizal root colonization were observed in either nutrient regimen with mycorrhizal inoculant addition. Petiole NO3-N concentration of lettuce plants grown with inorganic nutrient sources was greater than that of plants in organic regimens. Organic fertilizers and inoculant products resulted in comparable or positive impacts on plant growth and food crop quality in some treatment scenarios in these studies. The specific circumstances of crop production systems dictate whether plant growth response may occur from inoculant incorporation.
Keywords: Floriculture; Horticulture; Organic; Hydroponics; Microbial inoculants; Lettuce; Horticulture (0471)